2014
DOI: 10.1097/dss.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Delivery of Fractional Ablative Carbon Dioxide Laser Treatment for Acne Scars in Asian Patients Receiving Oral Isotretinoin

Abstract: Ablative CO2 fractional laser treatment for acne scarring seems to be safe regardless of isotretinoin use (10-60 mg/d). The authors' findings contribute to the discussion of whether oral isotretinoin treatment impairs wound healing after ablative laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
(20 reference statements)
1
34
0
3
Order By: Relevance
“…291,294 There are also retrospective studies and case reports demonstrating safety with laser hair removal, pulsed dye laser, and CO 2 laser. [295][296][297][298][299] While elective procedures should be delayed for 6 to 12 months when possible, careful consideration may be given on a case by case basis.…”
Section: Hormonal Agentsmentioning
confidence: 99%
“…291,294 There are also retrospective studies and case reports demonstrating safety with laser hair removal, pulsed dye laser, and CO 2 laser. [295][296][297][298][299] While elective procedures should be delayed for 6 to 12 months when possible, careful consideration may be given on a case by case basis.…”
Section: Hormonal Agentsmentioning
confidence: 99%
“…Given the lack of strong scientific evidence to substantiate the claims about poor wound healing in isotretinoin patients, recent literature has challenged the current recommendation to wait 6 months after the completion of oral isotretinoin treatment. There are a few case reports and retrospective cohort studies in the literature showing lack of adverse effects after laser procedures in isotretinoin patients . Khatri and his colleagues initially published case reports supporting safety and absence of complications such as atypical scarring or keloid formation after laser hair removal using long‐pulse diode, flash lamp, and long‐pulsed Nd:YAG lasers in patients receiving oral isotretinoin .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Khatri et al published a case that reported safety of ablative and NAFL resurfacing in isotretinoin patients . In the clinical context of acne scar revision, two retrospective studies (both with at‐least 20 subjects receiving 0.5–1 mg/kg of isotretinoin per day) reported that ablative carbon dioxide (CO 2 ) resurfacing for acne scarring conducted during and/or within 1–3 months of isotretinoin treatment is safe without any adverse effects on healing . Another study that evaluated treatment of acne and acne scars with concomitant use of 1550 nm NAFL with low‐dose isotretinoin (10 mg/day) suggested improved efficacy without any adverse effects when compared with controls .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal healing has been reported after laser‐assisted hair removal during treatment with oral isotretinoin, ablative fractionated laser for scars during or at 1–3 months post‐cessation of isotretinoin therapy, non‐ablative fractionated laser, dermaroller and microneedling radiofrequency, dermabrasion of a small facial area during treatment, full‐face combined medium‐depth chemical peel (Jessner's solution plus 35% TCA), followed by manual dermabrasion in areas with depressed scars, at 1–3 months after the completion of treatment with isotretinoin …”
Section: Discussionmentioning
confidence: 99%